Supported copper (I) catalyst from fish bone waste: An efficient, green and reusable catalyst for the click reaction toward N‐substituted 1, 2, 3‐TRIAZOLES. (5th July 2017) - Xiong, Xingquan; Tang, Zhongke; Sun, Zhaohong; Meng, Xiaoqing; Song, Sida; Quan, Zhilong
Abstract : An eco‐efficient, green, and multi‐gram procedure is presented for one‐pot multicomponent synthesis of N ‐substituted 1, 2, 3‐triazoles by using waste fishbone powders supported CuBr (FBPs‐CuBr) as catalyst. FBPs‐CuBr is found to be an efficient heterogeneous catalyst and a series of 1, 2, 3‐triazoles are obtained in moderate to excellent yields in water under MW irradiation (70–98%). It can be separated conveniently by a simple filtration and reused at least seven consecutive runs with a slight drop in the product yields. Furthermore, the desired product still could be obtained in 80% yield when the scale of the reaction was increased to 40.0 mmol. Abstract : Waste fishbone powders supported CuBr (FBPs‐CuBr) was developed for the synthesis of N ‐substituted 1, 2, 3‐triazoles in good to excellent yields under microwave‐assisted condition. The N ‐substituted 1, 2, 3‐triazole in the model reaction could be prepared in 80% yield even when the reaction scale was increased to 40 mmol.